Three-layer core-shell microcapsule and application thereof in water tree branch damage self-repairing insulating material

By introducing three-layer putaway microcapsules into epoxy resin insulating material, the magnetron targeting nature is distributed in the damaged area of ​​water branches, efficient self-repair of water branches is achieved, and the material performance is reduced and service life is shortened. question.

CN119391051APending Publication Date: 2025-02-07GUIZHOU POWER GRID CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411594421.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-09
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

Water branches damage in epoxy resin insulating materials is difficult to repair efficiently, resulting in reduced material performance and shortened service life.

Method used

Three-layer putaway microcapsules are used, with a structure such as linear alkylbenzenesulfonic acid, urea formaldehyde resin layer I, urea formaldehyde resin layer II and nano Fe3O4@SiO2 particle layer. The magnetron targeting distribution is achieved in the material connection or surface area. Self-repair of water branch damage.

Benefits of technology

Effectively repair water branch damage, restore insulation performance to 93.2% original value, extend the service life of the material, and reduce microcapsule consumption and preparation costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119391051A_ABST
    Figure CN119391051A_ABST
Patent Text Reader

Abstract

The invention discloses a three-layer core-shell microcapsule and application of the three-layer core-shell microcapsule in a water tree branch damage self-repairing insulating material. Aiming at the problem of degradation of water branches in an epoxy resin insulating material, the three-layer shell-core microcapsules are prepared innovatively by adopting an interfacial polymerization process, and the water branch damage self-repairing epoxy resin composite insulating material is prepared through high-temperature curing, so that water branch damage channels are efficiently repaired, and the service life of the insulating material is effectively prolonged; and long-term safe operation of power equipment is maintained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of insulating materials, and in particular relates to a three-layer core-shell microcapsule and an application thereof in a water tree damage self-repairing insulating material. Background Art

[0002] Epoxy resin insulation materials have many advantages such as high insulation performance, high structural strength, good sealing performance and low manufacturing cost. They have been widely used in power equipment and have developed rapidly. However, in actual application, epoxy resin insulation materials have limited toughness. After being subjected to electromagnetic, heat flow and mechanical vibration, they will inevitably produce micro-damage such as mechanical cracks or dendritic channels. Under the action of high electric fields, water molecules in the air and various environmental water around epoxy resin accumulate in micro-damages and continue to develop and expand, eventually causing water tree aging. Water tree aging is a permanent material degradation phenomenon that occurs inside epoxy resin insulation materials. It will cause the decline of many properties such as dielectric strength and tensile strength of epoxy resin, and even induce insulation breakdown, which will have a serious impact on the service life and operation safety of power equipment. However, water tree damage channels are usually micrometer-scale at the beginning of development, which cannot be observed with the naked eye, and the power equipment can only be shut down for inspection or repair and replacement of damaged materials, which is not conducive to the long-term stable operation of various power equipment. Inspired by the self-repair function of damaged living organisms in nature, if epoxy resin insulation materials are given the ability to self-repair and actively repair them in the early stages of water tree formation, the problem of water tree aging can be fundamentally solved and the service life of epoxy resin insulation materials can be effectively extended.

[0003] At present, the research on water dendrite aging in insulating materials mainly includes two aspects: one is to discuss the influencing factors and microscopic change process of water dendrite aging, and the other is to study the degradation mechanism and model construction of water dendrite aging. Studies have shown that water dendrites are electromechanical damage caused by the oxidation reaction of hydrophilic substances in the needle tip area and the local high electric field, and they continue to grow and develop with the diffusion and oxidation of hydrophilic substances. Its growth process can be divided into three stages. First, because the molecular chains of insulating materials are not tightly connected, the water in the humid environment gradually penetrates into the free volume holes inside the material under the action of the electric field. As the water inside the material accumulates more and more, the volume and number of water-filled holes increase, and the hydrophilic substances undergo oxidation reactions to induce water dendrites. At the same time, the water molecules in the holes exert electromechanical stress on the material under the action of the electric field, and connected filamentous damage channels begin to form between the holes. The hydrophilic substances further expand and oxidize, and finally develop into water dendrite damage channels. In addition, some studies have discussed the effects of saturated water content, applied electric field frequency, and electric field distortion rate on the degradation process of water dendrites, and obtained a three-dimensional view of water dendrites through a confocal laser scanning microscope based on the fluorescence colorimetric analysis method.

[0004] However, there is almost no research on the self-repair of water tree damage inside epoxy resin insulating materials. More research focuses on the self-repair of mechanical cracks and electrical tree damage in various insulating materials, such as nano-modification, non-autonomous repair based on reversible covalent bonds such as reversible acylhydrazone bonds and reversible C-NO bonds, non-autonomous self-repair based on reversible non-covalent bonds such as hydrogen bonds and metal ligands, microcapsules, bionic microvessels, etc. The above self-repair methods have effectively solved the problem of mechanical cracks and electrical tree degradation damage in insulating materials, but how to apply the above technical means to solve the problem of water tree damage in epoxy resin insulating materials still requires in-depth thinking and research. Therefore, it is of great significance to study a water tree damage self-repairing epoxy resin composite insulating material and its preparation method.

[0005] Epoxy resin insulation materials will inevitably produce water tree damage during practical applications, but there is currently a lack of truly effective solutions to the problem of epoxy resin water tree damage. Most studies on water tree damage focus on discussing the influencing factors and microscopic changes of water tree damage aging, as well as studying the degradation mechanism and model construction of water tree damage aging, but there is a lack of corresponding research on how to efficiently repair water tree damage. The degradation process of water tree damage in epoxy resin insulation materials involves multiple aspects such as local discharge, local thermal stress concentration, chemical decomposition, and mechanical fatigue. How to achieve efficient repair of water tree damage channels is a huge challenge.

[0006] The existing microcapsule self-repairing technology has made a breakthrough in the field of epoxy resin self-repair. Although it has a good effect on the repair of mechanical cracks and electrical tree damage in epoxy resin, the formation mechanism of water tree damage caused by the coupling of electric and thermal forces is not exactly the same as the above damage. The existing microcapsule technology cannot solve the problem of epoxy resin insulation material degradation caused by the development of water tree damage. In addition, due to the single triggering mode and function of microcapsule self-repair, the triggering conditions are limited, and it is very easy to fail in the face of diverse natural environments. In order to achieve efficient self-repair of water tree damage in epoxy resin insulation materials, it is urgent to improve the existing technology and innovatively develop a self-repairing microcapsule for water tree damage.

[0007] Introducing self-healing microcapsules into epoxy resin insulating materials is equivalent to introducing impurities into epoxy resin. Since the composition and internal structure of the microcapsules are different from those of the epoxy resin matrix, structural defects of the epoxy resin will be caused, resulting in a reduction in many properties of the epoxy resin insulating materials, such as insulation performance, tensile strength, and AC breakdown field strength. This makes it impossible to achieve widespread application of the existing microcapsule self-healing technology in the industrial field. Moreover, since the dielectric properties of the microcapsules are weaker than those of epoxy resin, water tree aging is more likely to occur in the area near the microcapsules. If efficient self-repair is performed on the water tree branch damage channel at the beginning of its growth and development, it will have a negative impact on the epoxy resin insulating material.

[0008] When preparing epoxy resin composite materials, most of the time, microcapsules are evenly distributed in the epoxy resin. However, in the actual application of epoxy resin insulating materials, water tree damage will be concentrated in the joints or surface areas of the insulating materials. The existing technology not only cannot effectively solve the problem of water tree degradation in high insulation failure areas, but also causes many problems such as the overall performance of the epoxy tree is reduced, the consumption of microcapsules is large, and the preparation cost is high. Summary of the invention

[0009] The purpose of this section is to summarize some aspects of embodiments of the present invention and briefly introduce some preferred embodiments. Some simplifications or omissions may be made in this section and the specification abstract and the invention title of this application to avoid blurring the purpose of this section, the specification abstract and the invention title, and such simplifications or omissions cannot be used to limit the scope of the present invention.

[0010] In view of the above problems and / or the problems existing in the prior art, the present invention is proposed.

[0011] Therefore, the purpose of the present invention is to overcome the deficiencies in the prior art and provide a three-layer core-shell microcapsule, wherein: the three-layer core-shell microcapsule is a core-shell-shell-shell structure, which is composed of linear alkylbenzene sulfonic acid, urea-formaldehyde resin layer I, urea-formaldehyde resin layer II, and nano-Fe3O4@SiO2 particle layer from inside to outside;

[0012] Wherein, hexadecyltrimethoxysilane exists between the urea-formaldehyde resin layer I and the urea-formaldehyde resin layer II, and the mass ratio of the hexadecyltrimethoxysilane to the linear alkylbenzene sulfonic acid is 5:1 to 5:1.1.

[0013] As a preferred embodiment of the three-layer core-shell microcapsule of the present invention, the preparation method of the three-layer core-shell microcapsule is as follows:

[0014] Hexadecyltrimethoxysilane, emulsifier and single-layer core-shell microcapsules were added to deionized water, heated in a water bath at 50-60°C for 2h, resorcinol, ammonium chloride and nano-Fe3O4@SiO2 modified urea-formaldehyde dendron prepolymer were added in sequence, stirred, pH was adjusted to 3-3.2 with dilute hydrochloric acid, heated in a water bath at 60-65°C for 4-5h, washed several times, filtered and vacuum dried to obtain three-layer core-shell microcapsules;

[0015] The mass ratio of hexadecyltrimethoxysilane, emulsifier and single-layer core-shell microcapsule is 5:10:1.4-5:12:1.5, and the concentration of hexadecyltrimethoxysilane in deionized water is 40-50 g / L;

[0016] The mass ratio of the resorcinol, ammonium chloride and nano-Fe3O4@SiO2 modified urea-formaldehyde resin prepolymer is 2:1:5-2:1.5:5, and the concentration of the ammonium chloride in deionized water is 10-15 g / L.

[0017] As a preferred embodiment of the three-layer core-shell microcapsule of the present invention, the preparation method of the single-layer core-shell microcapsule is as follows:

[0018] Urea is dissolved in deionized water, nano-Fe3O4@SiO2 particles are added, and then formaldehyde solution is added, mixed thoroughly, and triethanolamine is added to adjust the solution pH to 8-9, and heated in a water bath at 60-65°C for 2-4 hours, allowed to stand, and cooled to room temperature. The obtained liquid is nano-Fe3O4@SiO2 modified urea-formaldehyde resin prepolymer;

[0019] Sodium dodecylbenzene sulfonate, linear alkylbenzene sulfonic acid and deionized water are fully mixed and heated in a water bath at 45-50°C for 1-1.5 hours. When the solution becomes a black emulsion, sodium hydroxide solution is slowly added dropwise to adjust the pH value to 9-10.5 to obtain solution I.

[0020] Add resorcinol, ammonium chloride and nano-Fe3O4@SiO2 modified urea-formaldehyde resin prepolymer into solution I, then add citric acid solution to adjust the pH to 3.1-3.3, react at 60-65°C for 2-4h, then wash with anhydrous ethanol and deionized water for multiple times, filter and vacuum dry to obtain single-layer core-shell microcapsules.

[0021] As a preferred embodiment of the three-layer core-shell microcapsule described in the present invention, the concentration of urea in deionized water is 50-60 g / L, the concentration of nano Fe3O4@SiO2 in deionized water is 50-60 g / L, the concentration of formaldehyde solution is 35-37%, and the volume ratio of deionized water to formaldehyde solution is 10:1-10:1.1.

[0022] As a preferred embodiment of the three-layer core-shell microcapsule described in the present invention, the mass ratio of sodium dodecylbenzene sulfonate to linear alkylbenzene sulfonic acid is 15:2-15:1, the concentration of linear alkylbenzene sulfonic acid in deionized water is 20-25 g / L, the concentration of sodium hydroxide solution is 40-50%, and the concentration of citric acid solution is 5-6%.

[0023] As a preferred embodiment of the three-layer core-shell microcapsule of the present invention, the preparation method of the nano Fe3O4@SiO2 particles is as follows:

[0024] Ferric chloride, trisodium citrate and sodium acetate are dissolved in ethylene glycol, heated at 230-250°C for 8-10 hours, and the supernatant is removed after standing. The precipitate is washed with anhydrous ethanol and deionized water for multiple times, and filtered under reduced pressure to obtain nano-Fe3O4 particles.

[0025] Nano-Fe3O4 particles were added into a mixed solution of anhydrous ethanol, ammonia water and tetraethyl silicate, heated in a water bath at 30-35°C, mixed evenly, and the precipitate was washed with anhydrous ethanol and deionized water for multiple times and filtered to obtain nano-Fe3O4@SiO2 particles.

[0026] As a preferred embodiment of the three-layer core-shell microcapsule of the present invention, the concentration of the ferric chloride in ethylene glycol is 20-30 g / L, and the mass ratio of the ferric chloride, trisodium citrate and sodium acetate is 5:2:10-5:3:12.

[0027] As a preferred embodiment of the three-layer core-shell microcapsule described in the present invention, the concentration of the nano-Fe3O4 particles in the mixed solution is 40-45 g / L, the volume ratio of the anhydrous ethanol, ammonia water and tetraethyl silicate is 30:7:32-30:10:35, and the concentration of the ammonia water is 25-28%.

[0028] Another object of the present invention is to overcome the deficiencies in the prior art and provide the application of the three-layer core-shell microcapsule in water tree damage self-repairing insulating materials, wherein: the application includes application in epoxy resin, polytetrafluoroethylene, polyimide, and silicone gel.

[0029] As a preferred scheme for the application of the three-layer core-shell microcapsules described in the present invention in the self-repairing insulating material for water tree damage, the three-layer core-shell microcapsules are applied to epoxy resin, and the three-layer core-shell microcapsules are added to the epoxy resin base liquid, the doping concentration of the three-layer core-shell microcapsules is 2-6wt%, and the magnetically controlled targeting of the three-layer core-shell microcapsules is verified by artificial magnetic field induction, and then vacuum degassing, vacuum curing, cooling, and demolding are carried out to obtain the water tree damage self-repairing epoxy resin composite insulating material, thereby realizing the self-repair of water tree damage.

[0030] Beneficial effects of the present invention:

[0031] (1) Good self-repair effect of water tree branches: The three-layer core-shell microcapsules in the present invention can effectively solve the problem of water tree damage in epoxy resin insulating materials. After repair, the insulation performance of the epoxy resin composite insulating material is restored to 93.2% of the original, extending the service life of the material.

[0032] (2) Low cost of composite insulating materials: The present invention introduces nano-Fe3O4@SiO2 particles to give the three-layer core-shell microcapsules magnetically controlled targeting properties, control the distribution of the three-layer core-shell microcapsules in the material, and make the three-layer core-shell microcapsules distributed mostly in the area with high probability of damage to water dendrites, that is, the connection or surface area of ​​the insulating material, effectively solving the problems of high consumption of microcapsules and high preparation cost.

[0033] (3) Little impact on the electrical properties of the material: The doping of the three-layer core-shell microcapsules in the epoxy resin insulating material has little effect on the performance of the material. When the doping concentration is 2wt%, the AC breakdown field strength of the insulating material is reduced to 91.5% of that of pure epoxy resin, and the dielectric constant is only slightly reduced, which basically does not affect the dielectric properties of the insulating material. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the following briefly introduces the drawings required for describing the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative labor. Among them:

[0035] Figure 1 This is a transmission electron microscope characterization image of the nano-Fe3O4@SiO2 particles in Example 1 of the present invention.

[0036] Figure 2 This is a scanning electron microscope image of the three-layer core-shell microcapsule in Example 1 of the present invention.

[0037] Figure 3 This is a structural diagram of the three-layer core-shell microcapsule in Example 1 of the present invention.

[0038] Figure 4 This is a comparison chart of the breakdown field strength of the epoxy resin composite insulating material in Examples 2-4 of the present invention and Comparative Example 1.

[0039] Figure 5 This is a comparison chart of the dielectric properties of microcapsules at different microcapsule doping concentrations in Examples 2-4 of the present invention and Comparative Example 1.

[0040] Figure 6 This is a diagram of water tree detection in epoxy resin insulating material using the water needle method in Examples 2-4 of the present invention and Comparative Example 1. DETAILED DESCRIPTION

[0041] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with the embodiments of the specification.

[0042] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.

[0043] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The term "in one embodiment" that appears in different places in this specification does not necessarily refer to the same embodiment, nor does it refer to a separate or selective embodiment that is mutually exclusive with other embodiments.

[0044] The breakdown test method of the insulating material in the present invention is as follows: the thickness of the test sample is measured before the experiment, and the test sample is placed in a test tank, and the high-voltage electrode and the ground electrode are connected respectively. The test tank is filled with insulating oil, which can effectively prevent the test sample from flashing over along the surface. During the experiment, an AC voltage is applied to the electrodes through an AC test transformer and a voltage regulator until the test sample breaks down. After the test sample breaks down, its breakdown voltage is recorded, and then its breakdown field strength is calculated. In order to avoid interference from space charges, the breakdown test interval is set to 5 minutes, and the breakdown test of each composite insulating material is repeated 12 times. Finally, the test data are summarized and recorded, and the Weibull distribution diagram of the breakdown field strength of the composite insulating material is drawn using origin.

[0045] The dielectric property test method of the insulating material in the present invention is to use a broadband dielectric impedance spectrometer to test the dielectric property, and apply a frequency range of 10 -1 ~10 -6 The AC voltage of Hz is used, and the amplitude and phase of the current flowing through the test sample are recorded in time. The same experimental sample is tested 5 times and the average value is taken. After that, the experimental data is processed and the image is drawn to obtain the relative dielectric constant curve of the composite insulating material.

[0046] The water tree damage self-repair test method of the insulating material in the present invention is as follows: the water tree test device is mainly composed of an AC voltage regulator, a test transformer, a 5kV protection resistor, an AC voltage divider, a NaCl sample tank, an oscilloscope, and a real-time microscopic observation system. Before the experiment, a needle with a curvature radius of 20 is embedded in an epoxy resin composite insulating material. The needle electrode can simulate the internal defects of the epoxy resin, and can complete the entire process from the initiation of water tree branches to the failure of the insulating material in a relatively short period of time. The time required from the beginning of the growth of the water tree branches to the breakdown of the epoxy resin insulation is generally 1525min. During the experiment, a sample with a size of 2cm×2cm×3mm is placed in a NaCl solution with a concentration of 1mol / L. The needle is connected to a high-voltage electrode. The growth and development of water tree branches in the epoxy resin composite insulating material is observed through a real-time microscopic device, and a microscope image is taken.

[0047] Example 1

[0048] This embodiment provides a method for preparing a three-layer core-shell microcapsule, which comprises the following steps:

[0049] 1) Preparation of nano Fe3O4@SiO2 particles:

[0050] 5g of ferric chloride, 2g of trisodium citrate and 10g of sodium acetate were completely dissolved in 180ml of ethylene glycol by magnetic stirring for 4h, the mass ratio of the three was 5:2:10, and the concentration of ferric chloride was 27.78g / L. Then the mixed solution was heated at 230℃ for 8h, and the supernatant was removed after standing for 2h. After washing with anhydrous ethanol and deionized water for many times, nano-Fe3O4 particles were obtained by vacuum filtration.

[0051] 3g of nano-Fe3O4 particles, 30ml of anhydrous ethanol, 7ml of 25% ammonia water and 32ml of tetraethyl silicate were heated in a 30°C water bath. The concentration of nano-Fe3O4 particles was 43.5g / L, and the volume ratio of anhydrous ethanol, ammonia water and tetraethyl silicate was 30:7:32. During this process, magnetic stirring was used to make them evenly mixed, and then they were washed with anhydrous ethanol and deionized water several times and filtered to obtain nano-Fe3O4@SiO2 particles.

[0052] Dissolve 5g urea in 100ml deionized water, the urea concentration is 50g / L, then add 5g nano Fe3O4@SiO2 particles, the concentration of nano Fe3O4@SiO2 particles is 50g / L, then add 10ml of 37% formaldehyde solution, stir magnetically for 3h and mix the solution thoroughly. Use a dropper to slowly add triethanolamine to the beaker to adjust the pH of the solution to 8. Then heat the mixed solution in a water bath, stir at 60℃ for 2h to allow the material to react fully, and after the reaction is completed, let the solution stand and wait for it to cool to room temperature. The resulting liquid is nano Fe3O4@SiO2 modified urea-formaldehyde resin prepolymer, which is black and has a certain viscosity.

[0053] 2) Preparation of single-layer core-shell microcapsules:

[0054] Sodium dodecylbenzene sulfonate (SDBS) was selected as an emulsifier, and anionic surfactant linear alkylbenzene sulfonic acid (LABSA) was selected as a catalyst. 15g of emulsifier SDBD, 1g of catalyst LABSA and 50mL of deionized water were magnetically stirred to mix the solution thoroughly and heated in a water bath at 45℃. The concentration of LABSA was 20g / L, and the mass ratio of the two was 15:1. The experimental process lasted for 1h. When the mixed solution was a black emulsion, a 50% sodium hydroxide solution was slowly added with a dropper to adjust the pH value of the mixed solution to 9. After the pH value of the solution stabilized, resorcinol, ammonium chloride and urea-formaldehyde resin prepolymer were added to the solution, and then the pH of the mixed solution was reduced to 3.2 by adding a 6% citric acid solution, and magnetic stirring was continued at 60℃ for 2h. After the reaction was completed, the mixed solution was washed with anhydrous ethanol and deionized water for multiple times, and then the single-layer core-shell microcapsules were obtained by suction filtration and placed in a vacuum drying oven for drying.

[0055] 3) Preparation of three-layer core-shell microcapsules:

[0056] Hexadecyltrimethoxysilane (DTMS) was selected as the repair agent. 5g of the repair agent DTMS, 12g of the emulsifier and 1.5g of the single-layer core-shell microcapsules prepared in the above steps were added to 100ml of deionized water. The mass ratio of the three was 5:12:1.5, the concentration of DTMS was 50g / L, and the mass ratio of hexadecyltrimethoxysilane and linear alkylbenzene sulfonic acid was 5:1. The mixture was stirred for 2h in a 50℃ water bath to complete the reaction. 2g of resorcinol, 1g of ammonium chloride and 5g of urea-formaldehyde resin prepolymer were added in sequence and stirred for 30min. The mass ratio of the three was 2:1:5, and the concentration of ammonium chloride in deionized water was 10g / L. The pH value of the mixed solution was then reduced to 3.2 with dilute hydrochloric acid. The pH adjustment process should be controlled within 15min. After the pH of the solution stabilized, the mixed solution was heated to 60℃ by water bath heating. The process required 4h of reaction. After the reaction is completed, the mixed solution is washed and filtered for multiple times to obtain three-layer core-shell microcapsules, and then placed in a vacuum drying oven for drying to obtain three-layer core-shell microcapsules.

[0057] Figure 1 This is a transmission electron microscope characterization image of nano Fe3O4@SiO2 particles. It can be seen that the nano Fe3O4@SiO2 particles are uniform in size, with a concentrated particle size distribution. The particle morphology of the particles is mostly spherical or approximately spherical, and the particle aggregation degree is low, providing a higher surface area. Since Fe3O4 has a higher atomic number, it has a higher electron density under transmission electron microscopy characterization and appears dark. SiO2 has a lower electron density and appears light. In the transmission electron microscope characterization image, it can be clearly seen that the particles have a layer of light-colored SiO2 shell, and Fe3O4 is completely wrapped by it.

[0058] Figure 2 This is a scanning electron microscope characterization image of the three-layer core-shell microcapsule. It can be seen that the three-layer core-shell microcapsule is spherical as a whole, with a complete shape and no surface damage, indicating that the three-layer core-shell structure has good mechanical properties and plays a good supporting and protective role for the internal structure of the microcapsule. There are some depressions on the surface of the microcapsule, and its rough surface shell can enhance the compatibility between the microcapsule and the epoxy resin, enhance the connection between the two, and reduce the impact of the doping of the microcapsule on the various properties of the epoxy resin insulating material.

[0059] Figure 3The structure diagram of the three-layer core-shell microcapsule. It can be seen that the microcapsule finally prepared has a three-layer structure. The three-layer core-shell microcapsule is a core-shell-shell-shell structure, which is linear alkylbenzene sulfonic acid, urea-formaldehyde resin layer I, urea-formaldehyde resin layer II, and nano-Fe3O4@SiO2 particle layer from the inside to the outside. Nano-Fe3O4@SiO2 particles are attached to the outer surface of the microcapsule. Fe3O4 magnetic particles can give the microcapsule a magnetic targeting movement function. The SiO2 silicon layer can reduce the negative impact of Fe3O4 magnetic particles on the electrical insulation performance of the microcapsule. The introduction of SiO2 nanoparticles can enhance the interaction between the microcapsule and the epoxy resin matrix, making the two more closely connected. The inside of the three-layer core-shell microcapsule is a single-layer core-shell microcapsule and a repair liquid DTMS, and the catalyst LABSA is present in the single-layer core-shell microcapsule. Since the repair liquid needs to be hydrolyzed and condensed with water under the catalysis of the catalyst, the mass ratio of DTMS to LABSA in the microcapsule should be controlled at 5:1 to ensure that the reaction is complete. In addition, the three-layer shell structure can provide better mechanical support for the microcapsules, preventing the microcapsules from rupturing prematurely and causing repair failure.

[0060] Example 2

[0061] This embodiment provides a method for preparing a water tree damage self-repairing epoxy resin composite insulation material, specifically:

[0062] 100 g of resin monomer bisphenol A diglycidyl ether, 780 g of methyltetrahydrophthalic anhydride and 20 g of phenol were added into a beaker, and mixed evenly by magnetic stirring to obtain an insulating material base liquid, and then the three-layer core-shell microcapsules prepared in Example 1 were added into the insulating material base liquid, and the doping concentration of the microcapsules was 4 wt%.

[0063] Through artificial magnetic field induction, it is verified whether the microcapsules can move along the direction of the magnetic field and verify that the above-mentioned microcapsules have magnetically controlled targeting. Subsequently, the microcapsules are evenly mixed in the insulating material base liquid and vacuum degassed until no bubbles are generated in the base liquid during the degassing process before proceeding to the next step.

[0064] Finally, the mixed solution is poured into a mold and vacuum cured at 100°C. After curing, it is cooled to room temperature and demolded to obtain a molded water tree damage self-repairing epoxy resin composite insulation material.

[0065] Example 3

[0066] The difference between this embodiment and embodiment 2 is that the doping concentration of the three-layer core-shell microcapsule is adjusted to 2wt%. The other operation steps are the same as those in embodiment 1 to prepare the water tree damage self-repairing epoxy resin composite insulation material.

[0067] Example 4

[0068] The difference between this embodiment and embodiment 2 is that the doping concentration of the three-layer core-shell microcapsule is adjusted to 6wt%. The other operation steps are the same as those in embodiment 1 to prepare the water tree damage self-repairing epoxy resin composite insulation material.

[0069] Comparative Example 1

[0070] The difference between this comparative example and Example 2 is that the three-layer core-shell microcapsules are not doped, and the other operation steps are the same as those of Example 1 to obtain a pure epoxy resin material.

[0071] The insulating materials in Examples 2-4 and Comparative Example 1 were subjected to multiple tests including AC breakdown, dielectric constant, and water tree self-repair.

[0072] (1) AC breakdown characteristics test:

[0073] The AC breakdown characteristics of composite insulation materials were measured, and the breakdown field strength data of epoxy resin composite insulation materials were processed by Weibull statistical distribution after the experiment. The experimental results are shown in Figure 4 As shown. It can be seen that doping three-layer core-shell microcapsules in epoxy resin insulation materials will reduce the AC breakdown field strength of the insulation material, and as the doping concentration of the microcapsules increases, the AC breakdown field strength of the composite insulation material decreases. When the doping concentration of the microcapsules is 4.0wt%, the breakdown field strength is the largest.

[0074] When the doping concentration of microcapsules is 2.0wt%, the breakdown field strength of the composite insulating material is about 91.5% of that of pure epoxy resin, and the degree of change of the breakdown field strength is small; when the doping concentration of microcapsules is 6wt%, the breakdown field strength of the composite insulating material is reduced to 76.2% of that of pure epoxy resin. The significant reduction in the breakdown field strength seriously affects the insulation performance of the material. Since the breakdown field strength of the constituent materials of the microcapsules is lower than that of pure epoxy resin, the breakdown field strength of the composite insulating material tends to decrease after the introduction of microcapsules. The doping of microcapsules will introduce a large number of impurity groups, which are very easy to ionize under the action of high electric fields, increase the carrier concentration and increase the degree of collision ionization, resulting in accelerated failure of material insulation. The doping of microcapsules will also introduce defect structures, forming a low-density area between the microcapsules and the epoxy resin matrix. The defect structure distorts the electric field, and a relatively concentrated electric field will be formed in the low-density area, thereby generating new local discharge points and accelerating the failure of material insulation. When the concentration of microcapsules increases, too many microcapsules will cause the spacing between low-density areas to shrink or even touch, forming new conductive channels and destroying the structure of the insulating material, which is manifested as a significant reduction in the breakdown field strength of the composite insulating material.

[0075] (2) Dielectric properties test:

[0076] The relative dielectric constant of composite insulating materials, experimental results are as follows Figure 5As shown. It can be seen that the relative dielectric constants of pure epoxy resin and composite insulating materials decrease with the increase of frequency. The main reason is that the electronic polarization and impurity polarization inside the material can be synchronized with the external electric field at low frequency. The increase in frequency accelerates the change of the electric field, and the relaxation polarization comes too late to be established, so the relative dielectric constant of the material decreases. Epoxy resin composite insulating material has a smaller dielectric constant to reduce power consumption during transmission. With the increase of the doping amount of microcapsules, the dielectric constant shows a trend of first decreasing and then increasing. When the doping concentration of microcapsules is 2wt%, the relative dielectric constant of the composite insulating material is less than that of pure epoxy resin, but when the doping concentration of microcapsules is 4wt% and 6wt%, the relative dielectric constant of the composite insulating material is significantly greater than that of pure epoxy resin. When the doping concentration of microcapsules is low, due to the good compatibility of the microcapsule shell with the epoxy resin matrix, a microcapsule / epoxy resin cross-linking network is formed, which limits the dipole polarization in the material, forms a positive synergistic effect, and improves the dielectric properties of the material. The dielectric constant tends to decrease, but with the increase of the doping concentration of the microcapsules, a solid-solid interface region will be introduced between the microcapsules and the epoxy resin matrix, and a solid-liquid interface region will be formed between the shell and the core material of the microcapsules. The interlayer polarization brought by the interface region increases the leakage current of the material and thus reduces the dielectric properties.

[0077] (3) Water tree branch damage self-repair test:

[0078] The water needle method was used to observe water trees in epoxy resin insulation materials.

[0079] The experimental results are as follows Figure 6 As shown. It can be seen that the water tree starts from the tip of the needle electrode, and the water tree continues to expand outward due to charge injection and local discharge. When the electric tree develops and contacts the three-layer core-shell microcapsule, the microcapsule shell breaks, and the repair agent and catalyst in the microcapsule flow into the water tree channel under the capillary action and osmotic action. When it contacts the water tree, a chemical reaction occurs to generate new organic matter, which fills and solidifies the damaged channel, thereby restoring the performance of the insulating material. The insulation performance of the epoxy resin composite insulating material with a microcapsule doping concentration of 4wt% is restored to 93.2% of the original material.

[0080] In addition to the repair agent contained in the microcapsule itself, which can effectively repair the water dendrite damage, the larger dielectric constant of the microcapsule will affect the internal electric field distribution of the epoxy resin insulation material and affect the growth process of the water dendrite. At the same time, the impurities and interface areas introduced by the doped microcapsules will destroy the continuity of the original structure of the matrix, hinder the expansion of the water dendrites, and limit their size. At the same time, the nano-Fe3O4@SiO2 particles will produce a mechanical interlocking effect between the microcapsule and the polymer matrix, allowing the two to better combine, avoid microcapsule agglomeration, and further improve the repair rate.

[0081] Comparative Example 2

[0082] The difference between this comparative example and Example 1 is that the amount of ferric chloride is adjusted to 3 g and the concentration is 16.67 g / L. The other steps are the same as those in Example 1 to prepare microcapsules.

[0083] There are fewer nanoparticles attached to the microcapsules, and the magnetically controlled targeted movement function is poor. The targeted movement of the microcapsules cannot be completed within the curing time. Most of the microcapsules are still evenly distributed in the insulating material and cannot achieve a repair effect.

[0084] Comparative Example 3

[0085] The difference between this comparative example and Example 1 is that the amount of ferric chloride is adjusted to 7 g and the concentration is 38.89 g / L. The other steps are the same as those in Example 1 to prepare microcapsules.

[0086] Some microcapsules cannot be formed, and the breakdown voltage of the composite insulating material is greatly reduced, lower than 75% of the breakdown voltage of pure epoxy resin; the content of nano-Fe3O4@SiO2 particles is too low, which affects the formation of the cross-linked network between the microcapsules and the epoxy resin matrix, resulting in gap defects, and the insulation and electrical properties of the composite insulating material are also reduced.

[0087] In summary, the three-layer core-shell microcapsules in the present invention can effectively solve the problem of water tree damage in epoxy resin insulating materials. After repair, the insulation performance of epoxy resin composite insulating materials is restored to 93.2% of the original, extending the service life of the material; the present invention introduces nano Fe3O4@SiO2 particles, giving the three-layer core-shell microcapsules magnetic control targeting performance, controlling the distribution of the three-layer core-shell microcapsules in the material, so that the three-layer core-shell microcapsules are mostly distributed in the area with high probability of water tree damage, that is, the connection or surface area of ​​the insulating material, effectively solving the problems of high consumption and high preparation cost of the three-layer core-shell microcapsules. The doping of the three-layer core-shell microcapsules in the epoxy resin insulating material basically does not affect the material performance. When the doping concentration is 4wt%, the AC breakdown field strength of the insulating material is reduced to 91.5% of that of pure epoxy resin, and the dielectric constant is only slightly reduced, which basically does not affect the dielectric properties of the insulating material.

[0088] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention may be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present invention, which should all be included in the scope of the claims of the present invention.

Claims

1. A three-layer core-shell microcapsule, characterized in that: The three-layer core-shell microcapsule is a core-shell-shell-shell structure, which is composed of linear alkylbenzene sulfonic acid, urea-formaldehyde resin layer I, urea-formaldehyde resin layer II, and nano-Fe3O4@SiO2 particle layer from inside to outside; Wherein, hexadecyltrimethoxysilane exists between the urea-formaldehyde resin layer I and the urea-formaldehyde resin layer II, and the mass ratio of the hexadecyltrimethoxysilane to the linear alkylbenzene sulfonic acid is 5:1 to 5:1.

1.

2. The three-layer core-shell microcapsule according to claim 1, characterized in that: The preparation method of the three-layer core-shell microcapsule is: Hexadecyltrimethoxysilane, emulsifier and single-layer core-shell microcapsules were added to deionized water, heated in a water bath at 50-60°C for 2h, resorcinol, ammonium chloride and nano-Fe3O4@SiO2 modified urea-formaldehyde dendron prepolymer were added in sequence, stirred, pH was adjusted to 3-3.2 with dilute hydrochloric acid, heated in a water bath at 60-65°C for 4-5h, washed several times, filtered and vacuum dried to obtain three-layer core-shell microcapsules; The mass ratio of hexadecyltrimethoxysilane, emulsifier and single-layer core-shell microcapsule is 5:10:1.4-5:12:1.5, and the concentration of hexadecyltrimethoxysilane in deionized water is 40-50 g / L; The mass ratio of the resorcinol, ammonium chloride and nano-Fe3O4@SiO2 modified urea-formaldehyde resin prepolymer is 2:1:5-2:1.5:5, and the concentration of the ammonium chloride in deionized water is 10-15 g / L.

3. The three-layer core-shell microcapsule according to claim 2, characterized in that: The preparation method of the single-layer core-shell microcapsule is: Urea is dissolved in deionized water, nano-Fe3O4@SiO2 particles are added, and then formaldehyde solution is added, mixed thoroughly, and triethanolamine is added to adjust the solution pH to 8-9, and heated in a water bath at 60-65°C for 2-4 hours, allowed to stand, and cooled to room temperature. The obtained liquid is nano-Fe3O4@SiO2 modified urea-formaldehyde resin prepolymer; Sodium dodecylbenzene sulfonate, linear alkylbenzene sulfonic acid and deionized water are fully mixed and heated in a water bath at 45-50°C for 1-1.5 hours. When the solution becomes a black emulsion, sodium hydroxide solution is slowly added dropwise to adjust the pH value to 9-10.5 to obtain solution I. Add resorcinol, ammonium chloride and nano-Fe3O4@SiO2 modified urea-formaldehyde resin prepolymer into solution I, then add citric acid solution to adjust the pH to 3.1-3.3, react at 60-65°C for 2-4h, then wash with anhydrous ethanol and deionized water for multiple times, filter and vacuum dry to obtain single-layer core-shell microcapsules.

4. The three-layer core-shell microcapsule according to claim 3, characterized in that: The concentration of urea in deionized water is 50-60 g / L, the concentration of nano Fe3O4@SiO2 in deionized water is 50-60 g / L, the concentration of formaldehyde solution is 35-37%, and the volume ratio of deionized water to formaldehyde solution is 10:1-10:1.

1.

5. The three-layer core-shell microcapsule according to claim 3, characterized in that: The mass ratio of the sodium dodecylbenzene sulfonate to the linear alkylbenzene sulfonic acid is 15:2-15:1, the concentration of the linear alkylbenzene sulfonic acid in deionized water is 20-25 g / L, the concentration of the sodium hydroxide solution is 40-50%, and the concentration of the citric acid solution is 5-6%.

6. The three-layer core-shell microcapsule according to claim 3, characterized in that: The preparation method of the nano Fe3O4@SiO2 particles is as follows: Ferric chloride, trisodium citrate and sodium acetate are dissolved in ethylene glycol, heated at 230-250°C for 8-10 hours, and the supernatant is removed after standing. The precipitate is washed with anhydrous ethanol and deionized water for multiple times, and filtered under reduced pressure to obtain nano-Fe3O4 particles. Nano-Fe3O4 particles were added into a mixed solution of anhydrous ethanol, ammonia water and tetraethyl silicate, heated in a water bath at 30-35°C, mixed evenly, and the precipitate was washed with anhydrous ethanol and deionized water for multiple times and filtered to obtain nano-Fe3O4@SiO2 particles.

7. The three-layer core-shell microcapsule according to claim 6, characterized in that: The concentration of the ferric chloride in ethylene glycol is 20-30 g / L, and the mass ratio of the ferric chloride, trisodium citrate and sodium acetate is 5:2:10-5:3:

12.

8. The three-layer core-shell microcapsule according to claim 6, characterized in that: The concentration of the nano Fe3O4 particles in the mixed solution is 40-45 g / L, the volume ratio of the anhydrous ethanol, ammonia water and tetraethyl silicate is 30:7:32-30:10:35, and the concentration of the ammonia water is 25-28%.

9. Use of the three-layer core-shell microcapsule according to any one of claims 1 to 8 in water tree damage self-repairing insulating materials, characterized in that: The applications include applications in epoxy resins, polytetrafluoroethylene, polyimide, and silicone gels.

10. The use of the three-layer core-shell microcapsule as claimed in claim 9 in a water tree damage self-repairing insulating material, characterized in that: The three-layer core-shell microcapsule is applied to epoxy resin, and the three-layer core-shell microcapsule is added to the epoxy resin base liquid. The doping concentration of the three-layer core-shell microcapsule is 2-6wt%. The magnetically controlled targeting of the three-layer core-shell microcapsule is verified by artificial magnetic field induction, and then vacuum degassing, vacuum curing, cooling, and demolding are performed to obtain a water tree damage self-repairing epoxy resin composite insulating material, thereby realizing water tree damage self-repairing.